Methods for Writing Hijaiyah Alphabet Letters in Arabic Language Learning - Mustofa, Dedi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
The background of the problem in this study is that Arabic has several areas of proficiency, such as speaking proficiency, listening proficiency, reading proficiency and writing proficiency. Writing is a productive and expressive activity. In this writing activity, the writer must be skilled in utilizing graphology, language structure and vocabulary. This writing skill will not come automatically, but must go through a lot of regular practice and training. MTs Al Mubarok Uman Agung is one of the madrasahs located in Uman Agung, Bandar Mataram, Central Lampung whose students come from various educational backgrounds. This means that there are students who come from elementary schools and some from MI, from a preliminary study conducted by the author almost 70% of grade VII students of MTs Al Mubarok Uman Agung have an educational background from elementary schools who have never received Arabic lessons, while for writing Arabic they have never learned at all. Even some of the students have not memorized the hijaiyah letters and how to write them. With the differences in educational backgrounds, there are various problems concerning the learning of Arabic subjects, especially in the skills of writing Arabic texts. Among the students, there are still many who are new to Arabic from the madrasah. Therefore, it is necessary to use the right method in delivery, so that it can arouse students' interest and motivation in learning Arabic, especially in writing Arabic text skills. Keywords: Arabic, Writing Skills, Hijaiyah Letters.